(untitled) (American Journal of Research in Humanities and Social Sciences, 2025)
This article analyzes the key requirements for primary school native language and literacy lessons and the development of innovative pedagogical technologies. It emphasizes the necessity of applying modern methods and approaches, taking into account students’ individual characteristics to improve the effectiveness of the educational process.